Manajemen Kepemimpinan Transformasional dalam Tata Kelola International Islamic Boarding School - Zaki Ulien Nuha; Kardinal E Siregar; Iman Garish Muhammad; Muhammad Zaid Arsyad (Kartika: Jurnal Studi Keislaman, 2026)
The rapid development of education in the global era has encouraged Islamic educational institutions to maintain their Islamic values while preparing graduates who are able to compete in a wider environment. In this regard, transformational leadership is considered an important element in supporting effective institutional governance. However, studies focusing on transformational leadership within International Islamic Boarding Schools (IIBS) are still limited. This study aims to examine the construction of transformational leadership, human capital development strategies, and their implications for institutional quality and competitiveness. A qualitative approach with a field research design was employed. Data were collected through interviews with the principals of IIBS Al-Izzah Batu and IIBS Al-Wildan BSD and analyzed descriptively. The study found that transformational leadership is reflected in visionary leadership practices, exemplary behavior, the development of a quality-oriented culture, and the integration of Islamic values into institutional management. Efforts to develop human capital are carried out through competency improvement, coaching, motivation, and staff development programs. These practices contribute to improving educational quality, strengthening quality assurance systems, and producing graduates with strong academic, spiritual, and practical competencies. Additionally, they enhance the institution’s reputation and competitiveness at both national and international levels.